Comparison of various heat recovery options for compressed air energy storage system integrated with cascaded heat storage and organic Rankine cycle - Erdemir, Dogan; Dincer, Ibrahim (SPRINGER, 2023)
The present study deals with the development of compressed air energy storage options for off-peak electricity storage, along with heat recovery options. Three cases based on compressed air energy storage are considered for investigation and compared for evaluation. While case 1 considers only compressed air energy storage, case 2 includes cascaded heat storage for useful heat output. In case 3, compressed air energy storage is integrated with cascaded latent heat storage and organic Rankine cycle for power generation. The developed systems are analyzed based on the first and second laws of thermodynamics. Results indicate that heat recovery in the air compression process has great potential to improve the system performance. Heat storage option is included in the develped systems to provide opportunity for later use. For a 12 h charging period and a 6 h discharging period, the energy efficiencies for cases 1, 2 and 3 are determined to be 30.09%, 44.92% and 33.21%, respectively. The corresponding exergy efficiencies are then found to be 30.09%, 31.15% and 33.21%. While using the heat recovered as the useful output has improved the energetic performance by almost 15%, it has increased the exergetic performance by around 1%. When there is no heat demand on the site, case 3 has great potential to store off-peak electricity.
Keywords: Compressed air energy storage; CAES; Integrated system; Organic Rankine cycle; Energy; Exergy; Energy storage; Thermodynamics; Chemistry